2023
DOI: 10.1038/s41368-023-00223-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia support cartilage regeneration after injury

Abstract: In growing children, growth plate cartilage has limited self-repair ability upon fracture injury always leading to limb growth arrest. Interestingly, one type of fracture injuries within the growth plate achieve amazing self-healing, however, the mechanism is unclear. Using this type of fracture mouse model, we discovered the activation of Hedgehog (Hh) signaling in the injured growth plate, which could activate chondrocytes in growth plate and promote cartilage repair. Primary cilia are the central transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The classical Hh signaling pathway relies on primary cilia for transduction, which is indispensable for bone development and repair. Moreover, primary ciliary signals are observed in immune cells ( TAO et al, 2023 ) ( Figure 4 ).…”
Section: Molecular Interactions Between Immune Cells and Stem Cells W...mentioning
confidence: 99%
“…The classical Hh signaling pathway relies on primary cilia for transduction, which is indispensable for bone development and repair. Moreover, primary ciliary signals are observed in immune cells ( TAO et al, 2023 ) ( Figure 4 ).…”
Section: Molecular Interactions Between Immune Cells and Stem Cells W...mentioning
confidence: 99%
“…In addition, due to the unique composition of cartilage, its restoration following an injury proves highly challenging. Recently,Tao ( 81 ) found that activation of ciliated Hh signaling by Smoothened agonists (SAG) when the growth plate is damaged significantly accelerates growth plate repair after injury, and his further study found that chondrocytes in the resting and proliferating zones are dynamically ciliated during growth plate repair. Furthermore, conditional deletion of the cilia core gene Ift140 in cartilage disrupts cilia-mediated Hh signaling in the growth plate.…”
Section: The Role Of Primary Cilia In Bone Metabolismmentioning
confidence: 99%
“…This is true of neurons in multiple brain regions including the cerebellum, hippocampus, and cortex (Amador-Arjona et al, 2011; Breunig et al, 2008; Chizhikov et al, 2007; Han et al, 2008; Pruski et al, 2019; Spassky et al, 2008; Tong et al, 2014). Decreases in cell proliferation are seen in cilia mutants in other cell types as well including Müller glia cells, oligodendrocyte precursors, chondrocytes, outer annulus fibroblasts cells, osteoblasts, embryonic fibroblasts, and dental pulp stem cells (Cullen et al, 2021; Ferraro et al, 2015; Kitami et al, 2019; Li, Yang, et al, 2020; Noda et al, 2016; Pruski et al, 2019; Song et al, 2007; Tao et al, 2023; Yuan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%